2010
DOI: 10.1538/expanim.59.589
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Interleukin-6 and Cytokine-Induced Neutrophil Chemoattractant-1 on .ALPHA.2-Macroglobulin Production in Rats

Abstract: Abstract:We investigated the effects of interleukin-6 (IL-6) and cytokine-induced neutrophil chemoattractant-1 (CINC-1) on α 2 -macroglobulin (α2M) production in rats. IL-6-rich and CINC-1-rich fractions were separated from serum obtained from rats 12 h after injection with turpentine oil using gel-chromatography. Sexual dimorphism was observed in the peak levels of α2M after injection of IL-6-, CINC-1-, or a mixture of IL-6-and-CINC-1-rich fractions. No significant differences in α2M levels were observed in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
(17 reference statements)
3
8
0
Order By: Relevance
“…in the present study, The Cmax was also observed at 48 h after injection of turpentine oil before decreasing slowly in hepatopathic rats. The kinetics of α2M in experimental hepatopathic rats were similar to those in previous reports [8][9][10]13]. This study clarified that serum concentrations of α2M did not increase in hepatopathic rats when compared with nontreated rats.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…in the present study, The Cmax was also observed at 48 h after injection of turpentine oil before decreasing slowly in hepatopathic rats. The kinetics of α2M in experimental hepatopathic rats were similar to those in previous reports [8][9][10]13]. This study clarified that serum concentrations of α2M did not increase in hepatopathic rats when compared with nontreated rats.…”
Section: Discussionsupporting
confidence: 89%
“…The Cmax of α2M was observed at 48 h after inflammatory stimulation, e.g., injection of turpentine oil, inoculation with microorganisms or surgical treatment, before decreasing slowly [8][9][10]13]. in the present study, The Cmax was also observed at 48 h after injection of turpentine oil before decreasing slowly in hepatopathic rats.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations